2009
DOI: 10.3141/2127-19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Aspects of E* Test by Using Hot-Mix Asphalt Specimens with Varying Void Contents

Abstract: A dynamic modulus master curve for asphalt concrete is a critical input for flexible pavement design in the Mechanistic–Empirical Pavement Design Guide developed in NCHRP Project 1-37A, which has drawn much attention among asphalt technologists. The objectives in this study were ( a) to consider and compare different analysis techniques for construction of the master curve and ( b) to measure and analyze the effect of permanent strain on samples that have been evaluated with one of the simple performance tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 2 publications
1
12
0
Order By: Relevance
“…The combined effect resulted in a densification factor of 1.85 for the highest modulus (highest reduced frequencies) and 1.24 for the lowest modulus (lowest reduced frequencies) when air voids decreased from 11% to 8%. Similar results were obtained by Rowe et al by testing different air void contents from 11.3% to 2.3% (11). The resulting densification factor was 1.95 for the highest modulus and tended to decrease for low reduced frequencies.…”
Section: Evaluation Of Postcompaction Under Trafficsupporting
confidence: 87%
“…The combined effect resulted in a densification factor of 1.85 for the highest modulus (highest reduced frequencies) and 1.24 for the lowest modulus (lowest reduced frequencies) when air voids decreased from 11% to 8%. Similar results were obtained by Rowe et al by testing different air void contents from 11.3% to 2.3% (11). The resulting densification factor was 1.95 for the highest modulus and tended to decrease for low reduced frequencies.…”
Section: Evaluation Of Postcompaction Under Trafficsupporting
confidence: 87%
“…Seo, El Haggan, King, Lee, and Kim (2007) confirmed that increase in air voids results in lower |E * | and shorter fatigue life, and developed a model for predicting |E * | values from air void content. Rowe et al (2009) found the values of equilibrium and glassy modulus are significantly affected by the volumetric properties of mixture. Bari and Witczak (2005) Robinette, Breakah, Williams, and Bausano (2010) showed that nominal maximum aggregate size, test temperature and binder grade were the three main contributors to the variability in measured dynamic modulus.…”
Section: Factors Influencing Measured |E * | Valuesmentioning
confidence: 97%
“…Sigmoid function generally follows the trend of the measured and shifted |E * | values. However, other nonsymmetric functions are available that can provide better fit for some types of the HMA (Rowe, Baumgardner, & Sharrock, 2008;Rowe, Hakimzadeh, Blankenship, & Mahboub, 2009).…”
Section: Master Curvementioning
confidence: 98%
“…The generalized sigmoidal model (GSM) [ 41 , 42 ] and Huet-Sayegh model (HSM) [ 43 , 44 ] have been used successfully to characterize the mechanical behavior of asphalt mixtures, and this study uses the model to construct the dynamic modulus, storage modulus, and storage compliance master curves of asphalt mixtures. Based on the K-K relations, the phase angle, loss modulus, and loss compliance master curves can be derived from the GSM.…”
Section: Theoretical Backgroundmentioning
confidence: 99%